Thyroid and breast carcinomas in a patient with Pendred syndrome: a case report and literature review - Wu, Hongji; Xu, Jie; Xu, Ruzhong; Shi, Linlin; Xu, Lin; Zhou, Jin; Zheng, Haitao (Frontiers in Oncology, 2026)
BackgroundGoiter in the course of Pendred syndrome may in rare cases be associated with thyroid cancer (about 1% of all Pendred syndrome patients). The coexistence of Pendred syndrome with both thyroid and breast cancer is an even rarer condition reported in only one case.Case presentationWe report a case of a patient diagnosed with Pendred syndrome, who concurrently developed follicular thyroid cancer and breast cancer. After receiving four cycles of neoadjuvant THP (trastuzumab + pertuzumab + docetaxel) chemotherapy, the patient underwent left mastectomy and bilateral thyroidectomy. Postoperative pathology confirmed follicular thyroid carcinoma, while no residual malignancy was detected in the breast tissue. Genetic analysis of the SLC26A4 gene revealed mutations in intron 7 (c.919.2A>G) and exon 3 (c.170C>A) on chromosome 7. To minimize the risk of axillary metastasis, the patient received postoperative breast radiotherapy. At over one year of follow-up, there were no signs of recurrence for either cancer.ConclusionsThe coexistence of Pendred syndrome with both thyroid and breast carcinoma is extremely rare, and the underlying mechanisms remain uncertain. Current evidence does not support SLC26A4 as a driver oncogene, and the concurrence of malignancies may represent a coincidental finding rather than a causal association. Nonetheless, comprehensive genetic testing should be considered for patients with Pendred syndrome, and family-based screening is recommended once pathogenic SLC26A4 variants are identified. Long-term surveillance of the thyroid and breast is essential for early detection and timely management of potential malignancies in these patients.